Discriminating between Capacitor Bank Faults and External Faults for an Unbalanced Current Protection Relay Using DWT - Lertwanitrot, Praikanok; Ngaopitakkul, Atthapol (My University, 2020)
Capacitor faults are a common issue in modern-day power systems. Such systems employ a traditional mechanism that solely relies on unbalanced relays as an indicator of faults in capacitor banks; however, in the case of a relay trip, operators may find it difficult to identify the cause of these faults. To address this issue, this study aims to detect and discriminate between faults in the capacitor bank (i.e., internal faults) and those in the transmission line (i.e., external faults) by employing discrete wavelet transform (DWT). For this purpose, simulations were conducted using PSCAD software and modelled according to the 115-kV system from the Electricity Generating Authority of Thailand (EGAT). Furthermore, case studies involving faults with different phases, side and branch connections, row connections, inception angles, and blown fuses were considered. Moreover, the phase current, unbalanced current, and unbalanced voltage were analyzed to elucidate fault behaviors and the variation in the coefficient obtained via DWT; the unbalanced current and unbalanced voltage were used as design criteria for the proposed detection and relay operation algorithm. Real-world signals were employed to verify the accuracy of the proposed model. The results indicate that the proposed algorithm achieves satisfactory accuracy in terms of fault detection and the operation of relays in capacitor banks. The proposed algorithm is expected to enable an improvement in the performance of protection systems for capacitor banks in the near future.
Keywords: capacitor bank; detection; discrete wavelet transform; Fault; unbalance relay